Budaya Longko As a Character Building of Student Speech - Hakpantria; Trivena; Mersilina Luther Patintingan; Nanda Saputra (Lakhomi Journal Scientific Journal of Culture, 2022)
In order to develop or train students' characters through introduction and character development in the fundamental education, the Longko culture must be effectively utilized. One example is the application of speaking with older people as elementary school students or as adults when speaking or interacting with seniors. Utilize standard vocabulary to make yourself understood in conversations. The deskriptiv-qualitative methodology used in this study. The methodology used to analyze the data using Miles and Huberman's model consists of data collection, data reduction, data visualization, and the identification and verification of conclusions.